Confirmatory validation of the french version of the Duchenne Muscular Dystrophy module of the pediatric quality of life inventory (PedsQLTM3.0DMDfv) - Elisabeth Wallach; Virginie Ehlinger; Maelle Biotteau; Ulrike Walther-Louvier; Yann Péréon; Carole Vuillerot; Stephanie Fontaine; Pascal Sabouraud; Caroline Espil-Taris; Jean-Marie Cuisset; Vincent Laugel; Eloïse Baudou; et al. (BMC, 2023)
Abstract Duchenne Muscular Dystrophy (DMD) is a neuromuscular disease that inevitably leads to total loss of autonomy. The new therapeutic strategies aim to both improve survival and optimise quality of life. Evaluating quality of life is nevertheless a major challenge. No DMD-specific quality of life scale to exists in French. We therefore produced a French translation of the English Duchenne Muscular Dystrophy module of the Pediatric Quality of Life Inventory (PedsQLTMDMD) following international recommendations. The study objective was to carry out a confirmatory validation of the French version of the PedsQLTMDMD for paediatric patients with DMD, using French multicentre descriptive cross-sectional data. The sample consisted of 107 patients. Internal consistency was acceptable for proxy-assessments, with Cronbach's alpha coefficients above 0.70, except for the Treatment dimension. For self-assessments, internal consistency was acceptable only for the Daily Activities dimension. Our results showed poor metric qualities for the French version of the PedsQLTMDMD based on a sample of about 100 children, but these results remained consistent with those of the original validation. This confirms the interest of its use in clinical practice.